Nos rastros de Rota 66 e Abusado: o livro-reportagem e a tradição das narrativas realistas/naturalistas brasileiras - Nicoli Gloria de Tassis Guedes (2007)
This research investigates the main connections between the non-fiction books and the tradition of the Brazilian realistic/naturalistic narratives. From the rescue of the press and the news article´s history in the country, we identify in this publishing product some aesthetic, narrative and ideological traces proper of the dialogue between journalism and realistic/ naturalistic literature. Thus, we defend in this work that the conformation of the great news article in Brazil is previous to the movement of the new journalism and it is guided, many times, for the denunciation of the national problems, present also in a type of naturalistic narrative that had its height during the Military Regimen: the romance-news article. As well as in the realistic/naturalistic romances, we identify in the non-fiction books the effort to register the social transformations, to interpret the society and to give voice to the excluded groups. From the analysis of two books of the writer and journalist Caco Barcellos, we search the contours of this journalistic product and its contributions for the debate of the main questions that devastate our society.